(untitled) (Research, Society and Development, 2023)
The consumption of cigarettes or electronic systems containing nicotine and other substances is called smoking. This is the main risk factor for acquiring chronic diseases, responsible for six million deaths a year, being considered a neurobehavioral disease. The study aims to trace the epidemiological profile of the use of cigarettes and electronic nicotine-releasing devices in medical students in the 1st and 12th period of Faculdades Nova Esperança (FAMENE) and Ciências Médicas da Paraíba (FCM/PB). In addition to relating smoking with the age, sex and race of the participants; identify the degree of nicotine dependence of the participants and verify the anxiety scenario among the participants. For the study, a field research was carried out, of an observational nature, of the cross-sectional type, with a quantitative, descriptive approach, applied by students of the graduation course in Medicine at the Faculty of Medical Sciences of Paraíba. It was verified that the epidemiological profile of the smokers interviewed is characterized by the predominance of men, aged 20 to 25 years, white, with a low degree of nicotine dependence and anxiety, with a higher rate of beginner students who are addicted to smoking, when compared to the graduates.